Diagnostics of Cognitive Development in Children by Assessing Shared Intentionality in a Biotechnical System - I. V. Danilov; N. I. Kurakina; S. Mihailova (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Recent research shows that up to 17 % of children are diagnosed with cognitive developmental disorders. Early identification of developmental delay in children allows an earlier onset of treatment with greater efficiency. However, the modern diagnostic approach has limitations associated with the problem of correctly assessing behavioral markers of children. This classical assessing approach depends on specialists’ professionalism of and parents' competence in reporting the issue timely and informatively.Aim. Developing a computerized methodology and algorithm for estimating shared intentionality in mother-child dyads; designing a biotechnical system for the early diagnosis of a lag in children's cognitive development.Materials and methods. We analyze our own previous research, in which: 1) the goal was to measure the intellectual activity of a group while stimulating their shared intentionality; 2) the independent variable was the intellectual task; 3) the stimuli of shared intentionality were described. The method employs the mathematical apparatus of measurement theory, systems theory, and statistical methods of analysis.Results. The developed biotechnical system uses specific software for diagnosing cognitive delay in children during a 15-minute test. Two factors of the biotechnical system impact the object of assessment: an electromagnetic field for stimulating shared intentionality and an intellectual test. The system's software instantly provides the assessment results to the user (specialist or parents) in the form of recommendations understandable even to a non-specialist – it saves this database in a convenient form for further storage and processing.Conclusion. The advantage of the method is its unbiased computerized assessment, which can also diagnose subjects online, conversely to the classical approach based on behavioral markers. Another advantage of the assessment method is the possibility of diagnosing a lag in children's cognitive development at an earlier age, which does not yet imply verbal communication.